2009
DOI: 10.1007/s11259-009-9233-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between some oxidative Stress Biomarkers values in serum and plasma of clinically healthy adult camels (Camelus dromedarius) in Iran

Abstract: In this study, we measured some oxidative stress biomarkers, MDA and total thiol groups content in plasma along by this parameters in serum and Ferric Reducing Ability of Plasma (FRAP) of camels. The present study was undertaken first to establish a background of free radical damage status and second to comparison these levels in serum and plasma. To accomplish this, blood samples from 50 male Dromedary clinically healthy adult camels aged 24-48 months were collected. The correlation between serum and plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
8
3
Order By: Relevance
“…The mean Cu content of egg yolk was higher than that in the egg white for all the strains. The mean range of Cu content in the study of Salar‐Amoli and Ali‐Esfahani (2015) was 1.110–9.510 mg/kg, which was higher than the data obtained by this study. These discrepancies could be attributed to the different sampling procedures, sampling area and diet.…”
Section: Resultscontrasting
confidence: 84%
“…The mean Cu content of egg yolk was higher than that in the egg white for all the strains. The mean range of Cu content in the study of Salar‐Amoli and Ali‐Esfahani (2015) was 1.110–9.510 mg/kg, which was higher than the data obtained by this study. These discrepancies could be attributed to the different sampling procedures, sampling area and diet.…”
Section: Resultscontrasting
confidence: 84%
“…China (Zheng et al, 2007), and some other studies such as Nigeria (Fakayode & Olu-Owolabi, 2003), Canada (Kirkpatrick & Coffin, 1975), Pakistan (Khan & Naeem, 2006), and Iran (44) although were upper than those studies, they were still under the limitation. Two studies in Iran (Farahani et al, 2015;Salar-Amoli & Ali-Esfahani, 2015) and a study in Turkey (Uluozlu et al, 2009) were above the cadmium limits. (Table 3).…”
Section: Re Sults and Discussionmentioning
confidence: 97%
“…Collectively, the hematological and biochemical results in this study might indicate that the decline in serum biochemical parameters started later than the cellular alteration. Estimation of the enzymatic antioxidants activities, such as GSH-Px and SOD [29] as well as estimation of serum CAT [30] was a mean of evaluating oxidative stress. It was found that GSH -PX serum activity in infested donkeys decreased in January, February and March, SOD decreased in December, January and February while CAT activity decreased in all the months of the study.…”
Section: Discussionmentioning
confidence: 99%